Pengaruh Tingkat Pendidikan dan Pelatihan Terhadap Produktivitas Kerja Karyawan Pada RSD Ketapang Sampang - Haerul Anam; Budi Wahono; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study was to determine the effect of the level of education and training on the work productivity of Ketapang Sampang Hospital employees. This research is a quantitative research with technical data collection using a questionnaire. The sample in this study amounted to 57 respondents. The place of this research is the Ketapang Hospital employee on Jl. Raya Ketapang – Sampang No. 7, Ketapang, Mandirejo, Ketapang Bar., Sampang Ketapang Regency, East Java, 69261. The sampling technique used was the accident sampling method. Processing of primary data using analysis of Statistical Package for Social Science (SPSS) version 25. Techniques with multiple regression analysis method. The results of this study indicate that simultaneously the level of education and training variables have a significant effect on work productivity variables, while partially the level of education has a positive but not significant effect on work productivity variables and training variables have a positive and significant effect on work productivity variables. Keywords : level of education, training and work productivitas finance